Glucocorticoids can reduce mortality in patients with severe community-acquired pneumonia: a systematic review and meta-analysis of randomized controlled trials - Xue Gu; Penglei Yang; Lina Yu; Jun Yuan; Ying Zhang; Zhou Yuan; Lianxin Chen; Xiaoli Zhang; Qihong Chen (European Journal of Medical Research)
Abstract Background Severe community-acquired pneumonia (sCAP) is associated with higher morbidity and mortality. The use of glucocorticoids to improve the prognosis of severe community-acquired pneumonia remains a topic of controversy. Methods Following the guidelines given in the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA), we conducted a systematic review and meta-analysis to evaluate the effects of glucocorticoids on mortality and duration of mechanical ventilation in patients with sCAP. Randomized controlled studies investigating the use of glucocorticoids in the treatment of sCAP were extracted from PubMed, Embase, Cochrane Library, and Web of Science. Statistical analysis was performed to compare the differences in in-hospital mortality, mechanical ventilation duration, gastrointestinal bleeding, secondary infection, and other outcome measures between the glucocorticoid group and the control group. Results A total of 8 studies involving 1769 patients were included in the analysis. The hospital mortality in the glucocorticoid group was significantly lower than that in the control group [8 studies, relative risk (RR) 0.59; 95% CI 0.47–0.76, p < 0.01. I 2 = 25%, low certainty]. The duration of mechanical ventilation in the glucocorticoid group was significantly shorter than that in the control group [Mean Difference (MD) −3.08; 95% CI −4.96 to −1.19, p < 0.01; I 2 = 0%, low certainty]. There was no significant difference in the incidence of gastrointestinal bleeding (RR 0.94; 95% CI 0.55–1.63, p = 0.84, I 2 = 0%, low certainty) or secondary infection (RR 0.85; 95% CI 0.58–1.25, p = 0.85, I 2 = 2%, moderate certainty) between the glucocorticoid group and the control group. In subgroup analysis, mortality was significantly lower in the hydrocortisone group compared to the control group (6.3% vs. 14.6%, RR 0.43; 95% CI 0.29–0.62, p < 0.01, I 2 = 0%, very low certainty). However, there was no significant difference in mortality between the methylprednisolone group and the control group (15.6% vs. 19.9%, RR 0.78; 95% CI 0.57–1.08, p = 0.14, I 2 = 0%, moderate certainty). Conclusion Glucocorticoids can reduce mortality in patients with sCAP, and the effect may vary depending on the type and the dose of glucocorticoids used. Additionally, glucocorticoid treatment can lead to a shorter duration of mechanical ventilation, as well as the length of ICU stay, without increasing the risk of gastrointestinal bleeding or secondary infection in patients with sCAP. PROSPERO registration: CRD42023416525.